Defining malnutrition: A plea to rethink. Issue 3 (June 2017) - Soeters, P.; Bozzetti, F.; Cynober, L.; Forbes, A.; Shenkin, A.; Sobotka, L.
Summary: In a recent consensus report in Clinical Nutrition the undernourished category of malnutrition was proposed to be defined and diagnosed on the basis of a low BMI or unintentional weight loss combined with low BMI or FFMI with certain cut off points. The definition was endorsed by ESPEN despite recent endorsement of a very different definition. The approach aims to assess whether nutritional intake is sufficient but is imprecise because a low BMI does not always indicate malnutrition and individuals with increasing BMI's may have decreasing FFM's. The pathophysiology of individuals, considered to be malnourished in rich countries and in areas with endemic malnutrition, results predominantly from deficient nutrition combined with infection/inflammation. Both elements jointly determine body composition and function and consequently outcome of disease, trauma or treatment. When following the consensus statement only an imprecise estimate is acquired of nutritional intake without knowing the impact of inflammation. Most importantly, functional abilities are not assessed. Consequently it will remain uncertain how well the individual can overcome stressful events, what the causes are of dysfunction, how to set priorities for treatment and how to predict the effect of nutritional support. We therefore advise to consider the pathophysiology of malnourished individuals leading to inclusion of the following elements in the definition of malnutrition: a disordered nutritional state resulting from a combination of inflammation and a negative nutrient balance, leading to changes in body composition, function and outcome. A precise diagnosis of malnutrition should be based on assessment of these elements.